Valorization of Material Wastes for Environmental, Energetic and Biomedical Applications - Gil Bravo, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The development of materials from industrial wastes has attracted the attention of the research community for years. A material's physico-chemical characteristics have specific impacts its properties and their application in environmental, energetic, and biomedical areas, such as in pollutant removal; CO2 capture; energy storage; catalytic oxidation and reduction processes; the conversion of biomass to biofuels; and drug delivery. Examples of such materials are activated carbons, clays, and zeolites, among others. The aim of this Special Issue is to collect the recent advances and progresses developed in this field considering valorised materials from industrial wastes and their applications in environmental, energetic, and biomedical areas.